Location as a Factor Influencing the Students’ Decisions-Making to Enroll at Private Higher Education Institutions: Financial Aid as Moderator using SmartPLS - Shamsudin, Mohd Farid; Ali, Aeshah Mohd; Ishak, Mohd Fikri; Kadir, Baharudin (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: This study aimed to evaluate factors that influence the students’ decision-making to enrol at a private HEI within the Malaysian context. Accordingly, the specific objectives of this study are presented as follows: (i) to determine the relationship between the location of institution and the students’ decision-making to enrol at a private HEI, (ii) to assess the moderating role of financial aid between location of institution with the students’ decision-making to enrol at a private HEI. Methodology: The underpinning theory applied in this study was Theory of Planned Behavior (TPB) applied for location of institution. Five hundred (500) questionnaires distributed on the first-year undergraduate students (in their first academic semester in 2018) at 23 selected private HEIs in Kuala Lumpur and Selangor. The Data were analyzed using SmartPLS 3 analytical tool to carry-out PLS-SEM. Results: Findings indicated result for direct effect revealed a positive significance relationship between LO and DM; while the result of interaction (moderation) assessment had confirmed that the FA played a significant moderation role on relationship path between LO and DM indicated by t and p values. Thus, hypothesis h1 and h1a developed for this study were accepted. Implications: A positive significance relationship between LO and DM indicated by path coefficient of  0.37; t-value of 9.778 and p-value of 0.000. The result of PLS-SEM run had showed that the was a small interaction (moderation) effect explained by path coefficient of  value of -0.071. Consequently, a further analysis on path significance were carried out utilizing bootstrapping routine had showed that p-value of 0.014 and t-value of 2. 464. Henceforth, the result of interaction (moderation) assessment had confirmed that the FA played a significant moderation role on relationship path between LO and DM indicated by t and p values that surpassed the minimum threshold of two-tailed test (p-value < 0.05 and t-value >1.96 ).